2012
DOI: 10.2337/db12-0393
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Protective Effect of Lactation on the Development of Type 2 Diabetes in Women With Recent Gestational Diabetes Mellitus

Abstract: Women with gestational diabetes mellitus (GDM) have a high risk of developing postpartum type 2 diabetes. Strategies to prevent postpartum type 2 diabetes are important to reduce the epidemic of diabetes and its societal impact. Breastfeeding was reported to improve early postpartum glucose tolerance and reduce the subsequent risk of type 2 diabetes. To investigate whether breastfeeding influences short- and long-term postpartum diabetes outcomes, women with GDM (n = 304) participating in the prospective Germa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
169
1
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(195 citation statements)
references
References 20 publications
3
169
1
16
Order By: Relevance
“…Early breastfeeding has been associated with improved glycaemic outcomes in infants born to women with diabetes in pregnancy (18,19) . On the maternal side, lack of breast-feeding is associated with developing type 2 diabetes (20) , with a dosedependent effect for longer duration and higher intensity associated with lower risk of postpartum diabetes among women with GDM history (21)(22)(23)(24)(25)(26) .…”
mentioning
confidence: 99%
“…Early breastfeeding has been associated with improved glycaemic outcomes in infants born to women with diabetes in pregnancy (18,19) . On the maternal side, lack of breast-feeding is associated with developing type 2 diabetes (20) , with a dosedependent effect for longer duration and higher intensity associated with lower risk of postpartum diabetes among women with GDM history (21)(22)(23)(24)(25)(26) .…”
mentioning
confidence: 99%
“…Consequently, it was hypothesised that the association between duration of lactation and maternal type 2 diabetes risk may be confounded by maternal BMI [7,8]. However, in our previous analysis [3] and in studies of healthy women [9,10], adjusting for BMI had no impact or a very small impact on the association between lactation and type 2 diabetes risk. Moreover, a recent population-based study demonstrated that healthy lifestyle behaviours, which may be more prevalent in lactating mothers, did not confound the association between lactation and type 2 diabetes risk [10].…”
Section: Introductionmentioning
confidence: 75%
“…However, there is increasing evidence to suggest that lactation also has longterm health benefits for the mother. We recently reported that lactation in women with gestational diabetes was associated with a considerable long-term reduction in the risk of developing type 2 diabetes postpartum [3]. This risk reduction was most pronounced in women who lactated for >3 months, and the beneficial effect of lactation on the risk of diabetes was apparent for up to 15 years postpartum [3].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Wydłużenie czasu trwania laktacji do 24 tygodni czyni te różnice znamiennymi statystycznie. Najlepsze efekty prewencji cukrzycy typu 2 i otyłości uzyskiwano przy utrzymywaniu karmienia z piersi przez co najmniej rok [16]. Mechanizm tego korzystnego oddziaływania laktacji nie został jeszcze ostatecznie określony.…”
Section: Wewnątrzmaciczna śMierć Płoduunclassified